Contemporary house design. (Köln : DAAB, 2009)
It is true, that our society is evolving at an increasingly rapid pace. Our way of life is changing along with our needs. In recent years the climate has been changing in a way that is perceptible for the first time in human existence. Therefore new building materials, groundbreaking techniques or a simple return to traditional forms of construction, together with carefully studied systems for saving energy and making the most of the resources afforded by nature, are conforming contemporary architecture. Passive energy-saving systems, sustainable materials and the concept of designs made to last decades are reactions to the growing awareness about the environment from the local to the global viewpoint. This book is a demonstration of how today's houses are integrating all these elements.
Keywords: Huizen